Jane Austen in Hollywood - Troost, Linda, 1957-; Greenfield, Sayre N., 1956- (University Press of Kentucky, 2001)
In 1995 and 1996 six film or television adaptations of Jane Austen's novels were produced-an unprecedented number. More amazing, all were critical and/or box office successes. What accounts for this explosion of interest? Much of the appeal of these films lies in our nostalgic desire at the end of the millennium for an age of greater politeness and sexual reticence. Austen's ridicule of deceit and pretentiousness also appeals to our fin de siècle sensibilities. The novels were changed, however, to enhance their appeal to a wide popular audience, and the revisions reveal much about our own cult.